THE EFFECT OF USING MNEMONIC STRATEGIES ON STUDENTS’ VOCABULARY ACHIEVEMENT AT SMPN 2 RAHA - Ratnasari, Wa Ode; Nurnia, Nurnia; Fatmawati, Wa Ode (Journal of Teaching of English, 2020)
Most  of  the  students  felt  difficult  in  learning  a  language because they had little vocabulary. It was caused by the students were easy forgetting new words they had learned. Therefore, this study was conducted to investigate whether there was any significant effect of using Mnemonic strategies on students’ vocabulary achievements at the seventh grade students of SMPN 2 Raha. This research used quasi experimental design and the population was all seventh grade students of SMPN 2 Raha in academic year 2017/2018. The samples of this study were class VII11 as the experimental group and VII10 as the control group. The research instrument was using 40 questions of vocabulary test. To collect the data, the researcher gave pre-test, taught by Mnemonic strategies, and gave post-test.  There were four techniques that applied in the learning process were rhyme, keyword, visualization, and narrative chain. The result showed students’ mean score in experimental group was 53.54 and 74.71 at post-test, while mean score in control group was 57.27 and 68.75 in post-test. Based on the calculation of T-test, score of tcount  = 5.828 was higher than ttable   =  2.00  and  the  pvalue   =  0.000  was  lower  than = 0.05. Therefore, could be concluded that there was a significant effect of using mnemonic strategies on students’ vocabulary achievement at the seventh grade students of SMPN 2 Raha.